Collaboration-Oriented Culture Towards Sustainability Report Quality: The Role of Competitive Pressure - Atika, Atika; Prihastiwi, Diah Agustina; Aosiliana, Putri; Puspitasari, Fenny (Universitas Negeri Yogyakarta, 2025)
This research examines the impact of a collaboration-oriented culture on the quality of sustainability reports and the role of competitive pressure on this relationship. This quantitative research applies multiple regression analysis and moderated regression analysis to a sample of companies listed on the Indonesia Stock Exchange and the Sri Kehati index for the 2020-2022 period. Research data was obtained from the company's annual report and sustainability report. Research findings show that collaboration-oriented culture has a negative effect on the quality of sustainability reports. Competitive pressure was not found to weaken the negative effect of collaboration-oriented culture on the quality of sustainability reports. These findings indicate that the high and low competitive pressures faced by companies in their industry are unable to encourage companies to produce better-quality sustainability reports. This research has implications for companies to loosen collaboration-oriented culture to improve the quality of sustainability reports. This research also contributes to regulators (Indonesian Institute of Accountants and Financial Services Authority) to prepare sustainability report standards to improve the quality and comparability of reports. Keywords: Collaboration-Oriented Culture, Sustainability Report Quality, Competitive Pressure ABSTRAK Riset ini mengkaji dampak collaboration-oriented culture terhadap kualitas sustainability report serta peran tekanan kompetisi terhadap hubungan tersebut. Riset kuantitatif ini menerapkan analisis regresi berganda dan moderated regression analysis untuk sampel perusahaan yang terdaftar di Bursa Efek Indonesia dan indeks Sri Kehati periode 2020-2022. Data riset diperoleh dari annual report dan sustainability report perusahaan. Temuan riset menunjukkan collaboration-oriented culture berpengaruh negatif terhadap kualitas sustainability report. Tekanan kompetisi tidak ditemukan memperlemah pengaruh negatif collaboration-oriented culture terhadap kualitas sustainability report. Temuan tersebut menunjukkan bahwa tinggi rendahnya tekanan kompetisi yang dihadapi perusahaan pada industrinya tidak mampu mendorong perusahaan untuk menghasilkan sustainability report yang lebih berkualitas. Penelitian ini berimplikasi pada perusahaan untuk melonggarkan collaboration-oriented culture dalam rangka meningkatkan kualitas sustainability report. Penelitian ini juga memberikan kontribusi kepada regulator (Ikatan Akuntan Indonesia maupun Otoritas Jasa Keuangan) untuk menyusun standar sustainability report dalam rangka meningkatkan kualitas maupun komparabilitas laporan. Kata Kunci: Budaya Berorientasi Kolaborasi, Kualitas Laporan Keberlanjutan, Tekanan Kompetisi